Risk factors for multi-resistant aeruginous pseudomonas infection in patients with pneumonia associated with mechanical ventilation of the intensive care unit. Multicentric study - Jáuregui-Rojas, Paola (2021)
Objective: Determine the risk factors for multidrug-resistant Pseudomonas aeruginosa infection in patients with pneumonia associated with mechanical ventilation in the intensive care unit. Material and Methods: An observational, analytical, retrospective, case-control study was carried out in which 84 medical records of patients aged ≥ 18 years with a diagnosis of ventilator-associated pneumonia were selected by simple randomization at the Alta Complejidad Hospital Virgen de la Puerta (HACVP) and Hospital Belén de Trujillo (HBT) during the period from January-2014 to December-2019. In the data analysis, the Chi-square test was used to determine the statistical significance of association in the study variables. Results: Age, use of prior broad-spectrum antibiotic therapy, use of urinary catheter, time of urinary catheter use, and postoperative abdominal surgery were significantly associated (P <0,05) with multidrug-resistant Pseudomonas aeruginosa infection in patients with pneumonia associated with intensive care unit mechanical ventilation. Urinary catheter exposure time is a risk factor for multidrug-resistant Pseudomonas aeruginosa infection (p <0.001). Conclusions: The time of use of the urinary catheter for more than 7 days without change the catheter is a risk factor for infection by multidrug-resistant Pseudomonas aeruginosa in patients with pneumonia associated with mechanical ventilation.